Climate variability in early expansions of Homo sapiens in light of the new record of micromammals in Misliya Cave, Israel. Issue 139 (February 2020) - Weissbrod, Lior; Weinstein-Evron, Mina
Abstract: In this study, we provide the first taphonomic and taxonomic descriptions of the micromammals from Misliya Cave, where recently a Homo sapiens hemimaxilla has been reported. This finding significantly extends the time frame for the out-of-Africa presence of anatomically modern humans. It also provides an opportunity to reassess variation in early modern human population responses to climate change in the Levantine sequence. Information on species ranking and diversity estimations (Shannon functions) is obtained from quantitative data across 31 Levantine assemblages and investigated in a broad comparative frame using multivariate analyses. Recent models of human-climate interactions in the late Early–Middle Paleolithic of the southern Levant have drawn heavily on on-site associations of human fossils with remains of micromammals. However, there has been little, if any, attempt to examine the long-term picture of how paleocommunities of micromammals responded qualitatively and quantitatively to climatic oscillations of the region by altering their compositional complexity. Consequently, our understanding is vastly limited in regard to the paleoecosystem functions that linked past precipitation shifts to changes in primary producers and consumers or as to the background climatic conditions that allowed for the development of highly nonanalog ancient communities in the region. Although previous studies argued for a correspondence between alternations in H. sapiens and Neanderthal occupations of the Levant and faunal shifts in key biostratigraphic indicator taxa (such as Euro-Siberian Ellobius versus Saharo-Arabian Mastomys and Arvicanthis ), our data indicate the likelihood that early H. sapiens populations (Misliya and Qafzeh hominins) persisted through high amplitudes of paleoecological and climatic oscillations. It is unlikely, given these results, that climate functioned as a significant filter of early modern human persistence and genetic interactions with Neanderthals in the Levant.